(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Coronary in-stent restenosis (ISR) remains clinically relevant in routine practice and is often detected in patients returning for repeat coronary angiography after prior percutaneous coronary intervention (PCI). Objective To determine the frequency of angiographically confirmed ISR and identify associated clinical and laboratory characteristics, including left ventricular ejection fraction (LVEF), in a real-world repeat-angiography cohort . Methods This multicenter retrospective registry included 1,005 adults from three PCI centers in Aktobe region (Kazakhstan) who underwent repeat coronary angiography in 2019-2023 and had a documented history of prior stent implantation. ISR was defined as ≥50% diameter stenosis within a previously implanted stent. Groups with and without ISR were compared using nonparametric and categorical tests; multivariable logistic regression assessed independent associations. Results ISR was identified in 138/1,005 patients (overall frequency 13.7%). Patients with ISR more often had diabetes, peripheral artery disease, prior CABG, and heart failure history, and more frequently underwent angiography in the setting of myocardial infarction. ISR was associated with higher creatinine and a higher prevalence of eGFR <60 mL/min/1.73 m², a more atherogenic lipid profile (higher LDL-C and non-HDL-C), and slightly lower LVEF. LDL-C target attainment (≤1.4 mmol/L) was low overall. Outpatient therapy patterns were broadly similar between groups; among patients with diabetes, SGLT2 inhibitor use was higher in the ISR group. In multivariable analysis, older age, obesity, and ACS presentation were associated with higher odds of ISR, while diabetes and eGFR <60 mL/ min/1.73 m² showed inverse associations, interpreted cautiously in the repeatangiography context (Nagelkerke R²=0.070). Conclusion In a real-world repeat-angiography cohort after prior PCI, angiographically confirmed ISR (≥50%) was detected in 13.7% and was linked to a higher comorbidity burden, less favorable renal and lipid profiles, and slightly lower LVEF, with low LDL-C goal attainment in routine practice. These findings support intensified secondary prevention and further analyses incorporating procedural/anatomical determinants and timing from index PCI. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 832-839